KARAKTERISTIK MATAAIR DAN PENGGUNAAN AIR DOMESTIK DI KECAMATAN GEMAWANG, KABUPATEN TEMANGGUNG - Firizqi, Febby; Irshabdillah, Muhammad Ridho; Prayogo, Edwin Suryo; Rahmawati, Aulia Ika (UI Scholars Hub, 2019)
Spring is the concentration of groundwater flow out on the surface. There are several factors that cause the emergence of springs such as contacts between geological formations, and slope changes. The aim of this research is to a) inventory the springs in Gemawang district; b) to test the water quality of the springs in the Gemawang district; c) to know the springs conservation efforts conducted by the community and Local Government of Gemawang district; d) to know the number of domestic water needs of each village in Gemawang district. The method used in this research is field survey to inventory the existing springs in study area and interview method to answer the 3rd and 4th objectives. The results obtained from this research are: a) the number of springs found in study site totalling 52 springs; b) the tested springs characteristics include DHL, pH, temperature, and discharge; c) Efforts to conserve water resources can be done by increasing the utilization of surface water and ground water, improving the efficiency of irrigation water, maintaining water quality according to its allocation; d) Water use for household needs include washing, eating/drinking, showering, watering plants, and washing vehicles.